(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article talked about psychological pressure of advertisement on a potential consumer, about advertisement motions that discredit advertisement activity; the question about responsibility of advertisers and the advertising profession before society raises.